Persepsi Mahasiswa Terhadap Pembelajaran Daring Matematika Ideal Di Masa Pandemi Covid-19 - Bertu Rianto Takaendengan; Asriadi Asriadi (Education and Learning Journal, 2021)
This study aims to determine student perceptions of the ideal mathematics learning during the covid-19 pandemic. This research is a qualitative descriptive study that was carried out using observation, questionnaire, and interview techniques with 36 students of mathematics education class 2020 at Gorontalo State University who had participated in online learning for 2 semesters. The results showed that mathematics learning carried out during the covid-19 pandemic was still not ideal with a percentage of 91.6% due to the nature of difficult and abstract mathematics material and there were several repeated obstacles that occurred in the online learning process, namely: 1) teachers were less proficient in the use of online platforms; 2) teaching is carried out using only sound (audio); 3) the internet network is less stable so that students cannot participate in online learning. The recommendations for the ideal mathematics learning are: 1) in the online learning process the teacher must be able to master (proficiently) use the online platform used; 2) teachers must be able to design innovative and fun learning by utilizing the features available on the platform or utilizing objects that are around students; 3) teachers can provide learning resources that can be accessed at any time so as to facilitate students in order not to miss the subject matter.